Refinement of the Asymptotics of Three Charged Quantum Particles Scattering Problem Solution of the Six-Dimensional Distorted Plane Wave Type - Levin, S. B. (Journal of mathematical sciences (New York, N.Y.), 2024)
In the present paper, we propose an asymptotic form at infinity in the configuration space for the quantum scattering problem solution of three three-dimensional like-charged particles, including the description of single and double rescattering, also in domains where one of Jacobi pair coordinates proves to be bounded.